2020
DOI: 10.3389/fnins.2020.00081
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Blood Circular RNAs as Potential Biomarkers for Acute Ischemic Stroke

Abstract: Many hospitals lack facilities for accurate diagnosis of acute ischemic stroke (AIS). Circular RNA (circRNA) is highly expressed in the brain and is closely associated with stroke. In this study, we examined whether the blood-borne circRNAs could be promising candidates as adjunctive diagnostic biomarkers and their pathophysiological roles after stroke. We profiled the blood circRNA expression in mice subjected to experimental focal cerebral ischemia and validated the selected circRNAs in AIS patients. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 49 publications
1
36
0
1
Order By: Relevance
“…These characteristics make circRNAs promising biomarkers in many human diseases [14]. In the stroke eld, circRNA expression pro le changes in IS have been described, supporting circRNAs as potential biomarkers and therapeutic targets in IS [21][22][23][24][25]. Additionally, two recent studies revealed that the circRNA expression pro les signi cantly changed after ICH in rat brain tissues [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics make circRNAs promising biomarkers in many human diseases [14]. In the stroke eld, circRNA expression pro le changes in IS have been described, supporting circRNAs as potential biomarkers and therapeutic targets in IS [21][22][23][24][25]. Additionally, two recent studies revealed that the circRNA expression pro les signi cantly changed after ICH in rat brain tissues [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that circRNAs could serve as potential biomarkers in peripheral blood in coronary artery disease, early preeclampsia and cancers [16][17][18][19][20]. Moreover, multiple recent studies have reported circRNA expression pro les changed in ischemic stroke (IS) [21][22][23][24][25], suggesting that circRNAs are potential biomarkers and therapeutic targets in IS. In addition, two recent studies reported that circRNA expression pro les are altered after ICH in rat brain tissue [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…As the blood‐brain barrier was impaired during acute ischaemic stroke, differentially expressed circRNAs enter the bloodstream and thereby can be used as biomarkers for evaluating the progression of stroke. A study profiling the expression of circRNAs in the blood of mice with induced focal ischaemic stroke suggested that circPHKA2 and circBBS2 were promising markers for diagnosing acute ischaemic stroke 25 . Plasma circDLGAP4 is thought to be a promising biomarker for the diagnosis and evaluation of ischaemic brain damage 13 .…”
Section: Discussionmentioning
confidence: 99%
“…While using rodent models, 128, 198, and 789 circRNAs were found to be significantly changed at 5 min, 3 h, and 24 h after IS in mice blood sample. After validation by IS patient blood sample, hsa-circ-0090002 and hsa-circ-0039457 were reported to be differentially downregulated [53]. Besides, after 45minute-transient middle cerebral artery occlusion (MCAO), circRNA microarrays revealed that 1027 circRNAs were significantly changed in 48 hours after reperfusion in the ischemic brain versus the sham group in which 914 circR-NAs were notably increased, while the other 113 were notably decreased.…”
Section: Circrnas and Stroke 61 Circrnas And Ismentioning
confidence: 99%
“…KEGG pathway analysis predicted that mmu-circRNA-015947 might be involved in apoptosis, metabolism and immune-related pathways, which are known to play a role in cerebral I/R injury [58]. The detailed information summary is shown in Table 1 [49][50][51][52][53][54][55][56][57][58]. Besides, circHECTD1 expression was upregulated in IS recurrence patients versus non-recurrence patients (160 : 160).…”
Section: Circrnas and Stroke 61 Circrnas And Ismentioning
confidence: 99%